If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56x + -4 = 52 Reorder the terms: -4 + 56x = 52 Solving -4 + 56x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 56x = 52 + 4 Combine like terms: -4 + 4 = 0 0 + 56x = 52 + 4 56x = 52 + 4 Combine like terms: 52 + 4 = 56 56x = 56 Divide each side by '56'. x = 1 Simplifying x = 1
| 6x^(2/3)-5x^(1/3)-1=0 | | 4d=5+3d | | 4z(2z-3)=2z-3 | | 30x^2-464x-2500=0 | | 5/6(T)=2/3 | | 2(4s+5)-4s=2(2s+1)-5 | | 38735=x+x(.27) | | 38735=x-x(.27) | | 10-(3z-4)=3-4z | | 6n-7=28.4 | | 484.50=x-x(.05) | | 23.20=x-x(0.20) | | -21-28+x=-37 | | 9x-7=44-8x | | 2w(6w-1)= | | 3c+4=-4c+16 | | 5(c+78)=9c(45-c)+12c | | 7x+9=2x+29 | | ln(x)=ln(27)+ln(15)+ln(36) | | -8+4(1+5n)=-6n+14 | | m^2-12m=0 | | 3y(3y-1)-3(2y)=2 | | 0.35x+0.05(12-x)=0.10(0) | | c+4=56 | | 3n+6.5=21.5 | | 4w=w+12 | | x(x+17)=-72 | | f(x)=ln(7) | | q+26=29 | | 7x+8=8x+20 | | 541x-64=-803 | | 6x-2(-5x-7)=-98 |